System Analysis and Implementation of Standard Operating Procedure (SOP) Towards Maximum Efficiency in Warehousing in Bekasi Raya - Dwita, Febrisi; Puspita, Retno Ayu (West Science Business and Management, 2025)
This study discusses the problem of operational efficiency in warehouses in the Bekasi Raya area which is not yet optimal due to the lack of structured warehouse management systems and inconsistent implementation of Standard Operating Procedures (SOPs). The purpose of this study is to analyze the warehouse management system implemented and evaluate the extent to which SOPs contribute to increasing efficiency. The urgency of the study lies in the vital role of Bekasi Raya as a national industrial and logistics area that demands an effective and professional warehousing system. The method used is a descriptive qualitative approach through observation, in-depth interviews, and SOP document studies in five purposively selected warehousing companies. The results of the study indicate that although most warehouses already have SOPs, their implementation is not optimal due to lack of training, periodic evaluations, and the lack of integration of SOPs with technology-based management systems. In conclusion, SOPs that are implemented consistently and integrated with the warehouse management system can significantly increase efficiency. Digitalization, periodic training, and ongoing supervision are needed to support maximum efficiency in warehouse operations.